What I Wish I Had Known: Examining Parent Accounts of Managing the Health of Their Child With Intellectual Disability - Thom Nevill; Jessica Keely; Rachel Skoss; Rachel Collins; Katherine Langdon; Jaquie Mills; Jenny Downs (Health Expectations)
ABSTRACT Background Appropriate support for the health of children with an intellectual disability by parents and healthcare professionals is pivotal, given the high risk of chronic conditions. However, there is limited research that has collected important insights from parents on their learnings for supporting their child's evolving healthcare needs. Aim This study focuses on parents' experiences and learnings from managing and supporting the health of their child with intellectual disability. It aims to understand what parents wish they had known earlier, the essential knowledge and skills they needed to manage their child's health. Method A qualitative study was carried out using semi‐structured interviews with 21 parents of adolescents and young people with intellectual disability. The children had chronic health conditions that fell into six health domains, including (1) difficulties with movement and physical activity, (2) epilepsy, (3) dental care, (4) respiratory health and infection, (5) behaviour, mental health or sleep and (6) gastrointestinal health. Results Thematic analysis yielded five themes: (1) optimising mutual engagement between healthcare professionals and families; (2) planning and practising effective healthcare; (3) having the right information at the right time; (4) finding the support that was needed and (5) navigating healthcare and disability systems. Over time, parents developed specific skills and knowledge for managing their child's health effectively. Some parents expressed regret for not seeking support and information about their child's health conditions earlier. Parents described how mutual engagement between healthcare professionals and parents optimised the management of their child's healthcare. Conclusion The study found that managing the health of a child with intellectual disability is complex. The themes were consistent across health comorbidities, indicating important common experiences. The themes aligned with conceptualisations of health literacy, suggesting that improving health literacy skills can help parents better manage their children's health conditions. Patient or Public Contribution We developed the project in consultation with members of the public who have lived experience of parenting a child with intellectual disability. They commented on the study aims, interview schedule, participant recruitment and provided feedback on the analysis and discussion.